2017
DOI: 10.3390/md15070232
|View full text |Cite
|
Sign up to set email alerts
|

Ladder-Shaped Ion Channel Ligands: Current State of Knowledge

Abstract: Ciguatoxins (CTX) and brevetoxins (BTX) are polycyclic ethereal compounds biosynthesized by the worldwide distributed planktonic and epibenthic dinoflagellates of Gambierdiscus and Karenia genera, correspondingly. Ciguatera, evoked by CTXs, is a type of ichthyosarcotoxism, which involves a variety of gastrointestinal and neurological symptoms, while BTXs cause so-called neurotoxic shellfish poisoning. Both types of toxins are reviewed together because of similar mechanisms of their action. These are the only m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 204 publications
(308 reference statements)
0
21
0
Order By: Relevance
“…Recent studies revealed that G. excentricus is one of the most toxic species known to date for production of both ciguatoxins (CTXs) and maitotoxins (MTXs) 3–7 . CTXs are the main known causative agents of CP 8 . Although they have very low oral potency, 7,9 MTXs are very toxic following intraperitoneal injection 10 and feeding studies by Kohli et al 11 in laboratory‐controlled conditions have shown they may accumulate in fish muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that G. excentricus is one of the most toxic species known to date for production of both ciguatoxins (CTXs) and maitotoxins (MTXs) 3–7 . CTXs are the main known causative agents of CP 8 . Although they have very low oral potency, 7,9 MTXs are very toxic following intraperitoneal injection 10 and feeding studies by Kohli et al 11 in laboratory‐controlled conditions have shown they may accumulate in fish muscle.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of this approach is the inability of ring expansion for ketone 52, presumably due to severe steric congestion of the 1,3-diaxial methyl groups. 40) These results demonstrate the synthetic utility of the oxiranyl anion strategy combined with the ring expansion reaction in the synthesis of polycyclic ether natural products. 42) causes the same characteristic rounding of cultured mouse neuroblastoma cells as brevetoxins A and B and shows cytotoxicity at a concentration of 5 µmol.…”
Section: Synthesis Of Seven-membered Ether Ring Systems By Ring Expanmentioning
confidence: 69%
“…The density of Gambierdiscus spp. in natural waters usually fluctuates widely within a short period; however, analyses of environmental factors such as temperature, salinity, or nutrients have not attributed these fluctuations to any of these factors [37]. It is possible that interactions with bacteria affect the population variation of Gambierdiscus spp.…”
Section: Discussionmentioning
confidence: 99%